Effect of High Concentration Alkali Treatment on the Mechanical and Structural Properties of Doyo Fibers (Curculigo Latifolia) - Setiawan, Ferry Bayu; Setyarini, Putu Hadi; Irawan, Yudy Surya (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2026)
The growing demand for sustainable materials has increased interest in natural fibers as eco-friendly reinforcements. Doyo fiber (Curculigo latifolia) from East Kalimantan remains insufficiently characterized despite its ecological potential. This study investigates the effect of alkali treatment concentration and immersion time on the mechanical and structural properties of doyo fibers. Fibers were treated using NaOH solutions (5–10%) and analyzed through tensile testing, Fourier transform infrared spectroscopy (FTIR), and field emission scanning electron microscopy (FESEM). Untreated fibers exhibited the highest tensile strength (176.83 MPa), while moderate treatment (5% NaOH for 90 min) preserved comparable strength (171.52 MPa) with improved surface activation. Aggressive treatment (10% NaOH) reduced tensile strength below 110 MPa due to cellulose degradation. These results demonstrate that alkali treatment requires careful optimization to balance performance enhancement and structural integrity.